Design and fabrication of portable solar cooker / Intanku Sofea Mohamad Zaidi - Mohamad Zaidi, Intanku Sofea (2023)
This project objectified performing a modified version of a portable solar cooker that has the same function as existing products while being much eco-friendlier and more reasonable in price. Using the materials aluminum as a substitute for using stainless steel metal will not only reduce the manufacturing cost by up to 70% but it will be effortless for the user to find spare parts if any element of the product goes awry. The product is fabricated with solar energy as its sole source of energy, which can be an additional point for individuals and communities that place concern for nature as their number one priority. This project discusses the material used, the time needed for the process, and the result obtained. In conclusion, based on the demonstration of the project, the authors discussed the advantages and points that need to be considered to make sure the process approximates the expected result .